2014
DOI: 10.13080/z-a.2014.101.009
|View full text |Cite
|
Sign up to set email alerts
|

Mulch type and application of manure and composts in strawberry (Fragaria × ananassa Duch.) production: impact on soil fertility and yield

Abstract: The objective of this research was to quantify the effect of the application of organic fertilizers: farmyard manure, vermicompost, spent mushroom compost, under two different ground cover management systems (black polyethylene and wheat straw mulch) on soil nutrient levels and strawberry yield during a two-year production cycle. The application of organic fertilizers, in the amounts equivalent to 170 kg ha -1 N, had the greatest impact on the concentration of available phosphorus, which was significantly high… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(9 citation statements)
references
References 26 publications
0
9
0
Order By: Relevance
“…This is evidenced by the results obtained by Siwek et al (2015), where the lowest nitrogen level (especially in the nitrate form) was recorded on the unprotected control site. In turn, Cabilovski et al (2014), in strawberry mulching with organic fertilization, reported higher concentrations of micronutrients under the surface of synthetic mulches compared to straw. Under the influence of the protective mulch of fodder radish, an increase in the number of soil macropores with a diameter of 50-500 μm was observed in the upper soil layer (0-10 cm) (Głąb and Kulig, 2008).…”
Section: Physical and Chemical Properties Of The Soilmentioning
confidence: 92%
See 1 more Smart Citation
“…This is evidenced by the results obtained by Siwek et al (2015), where the lowest nitrogen level (especially in the nitrate form) was recorded on the unprotected control site. In turn, Cabilovski et al (2014), in strawberry mulching with organic fertilization, reported higher concentrations of micronutrients under the surface of synthetic mulches compared to straw. Under the influence of the protective mulch of fodder radish, an increase in the number of soil macropores with a diameter of 50-500 μm was observed in the upper soil layer (0-10 cm) (Głąb and Kulig, 2008).…”
Section: Physical and Chemical Properties Of The Soilmentioning
confidence: 92%
“…Other materials include paper mulches, which are made of wrapping paper, waxed or treated otherwise, providing a cheaper alternative to straw (Haapala et al, 2014). Compost with animal excrement seems to be the best material in terms of the quantity of organic matter it contains (Cabilovski et al, 2014). Organic materials (such as straw, sawdust, bark, or peat) exhibit low bulk density of about 0.06-0.30 g cm -3 .…”
Section: Organic Mulchesmentioning
confidence: 99%
“…Mulching also improves plants growing media properties, which can positively influence plant growth and flowering during the growing season. Cabilovski et al [2014] reported that different composts mixed with the topsoil are used to improve soil fertility. On the other hand, mulch as a source of nutrients for urban plants is less preferred.…”
Section: Introductionmentioning
confidence: 99%
“…Textile, straw, sawdust and paper mulch types are also prefered due to their air and water permeability properties (Pop et al, 2013;Dobbs, 2003;Berglund et al, 2006;Skroch et al, 1992). It is reported that, some organic and inorganic materials could also be used as mulch material in strawberry cultivation (Birkeland et al, 2002;Cabilovski et al, 2014;Demirsoy et al, 2012;Kumar & Deyb, 2011;Bilck et al, 2010;Kuru, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Fertilizing is the most important factor for yield, quality and plant development in plant production. Organic fertilization is as important as inorganic fertilization for plant growth processes (Cabilovski et al, 2014). Organic fertilizers' harmful effects are not excessively when it applied high dosage cause of their narrow nutrition elements range.…”
Section: Introductionmentioning
confidence: 99%